2017
DOI: 10.17770/sie2017vol1.2325
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Sense of Belonging to the Country: Exploring a New Model

Abstract: This study explored new possibilities for measuring the sense of belonging to the country and investigated predictors of the sense of belonging to Latvia. Focusing on students’ sense of belonging to the country is explained by two reasons: 1) emigration is the main factor of depopulation in Latvia; 2) students’ intention to emigrate is the highest among other social groups. Studies in the field of community psychology present models of the sense of community and explore intentions to stay in a particular place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…In a study in Latvia, Kolesovs and Melne (2017) confirmed that predictors of a higher level of the sense of belonging to the country include a higher level of perceived opportunities for the fulfillment of personal goals (Nurmi, 2004(Nurmi, , 2013) and a more positive evaluation of the situation. Similar relationships were observed at the level of a community as a nested ecological system (Bronfenbrenner & Morris, 2006).…”
Section: Consequences and Predictors Of The Sense Of Belonging To A Cmentioning
confidence: 87%
See 3 more Smart Citations
“…In a study in Latvia, Kolesovs and Melne (2017) confirmed that predictors of a higher level of the sense of belonging to the country include a higher level of perceived opportunities for the fulfillment of personal goals (Nurmi, 2004(Nurmi, , 2013) and a more positive evaluation of the situation. Similar relationships were observed at the level of a community as a nested ecological system (Bronfenbrenner & Morris, 2006).…”
Section: Consequences and Predictors Of The Sense Of Belonging To A Cmentioning
confidence: 87%
“…The Sense of Belonging in Social Context Questionnaire (Kolesovs & Melne, 2017). The questionnaire was administered in Latvian and aimed at revealing the generalized sense of belonging with an emphasis on its spatiotemporal component.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying a sense of belonging within a higher education context is gaining currency (e.g. Kolesovs and Melne 2017). This is actuated by the complex challenges that characterise higher education.…”
Section: Sense Of Belonging and The Academic Contextmentioning
confidence: 99%